RELEVANSI TANAH ADAT DALAM UPACARA ADAT DHEKOLEGA DALAM HAL MENJAGA TATANAN HIDUP MASYARAKAT - Soro, Elroswit E.Teresa Gae; Rodriguez P.M. Ropa, Alfonsus; Kause, Nina Sumirna; Djahamouw, Erick Edgar Davidson; Nikolaus , Ermes; Maran , Mary Grace Megumi; Lay, Benediktus Peter (Gapenas Publisher, 2025)
Customary land has a very important meaning in the lives of indigenous peoples of Indonesia, including in the context of the Dheko Lega ceremony in Ngoranale Village, Bajawa District, Ngada Regency, East Nusa Tenggara. In the Bajawa indigenous people, land is not only understood as an economic asset, but also as a symbol of identity, ancestral heritage, spiritual connections, and sources of livelihood that are deeply rooted in social and cultural structures. The Dheko Lega ceremony is an important customary ritual carried out to transfer customary responsibilities and land management rights from the mother's family to the father's family, especially in situations where there are no daughters in the father's family. One of the important elements of this ceremony is the handover of land as a form of legitimacy for the status of customarily adopted children. If this ceremony is carried out without the handing over of the land, it will arise due to customary law, including the invalidity of the ceremony, the loss of inheritance rights and land rights, as well as the potential for social conflicts and customary sanctions. Therefore, customary land has a strategic position in maintaining the continuity of kinship, cultural preservation, and social order of the Bajawa indigenous people, so that respect for all customary elements in Dheko Lega is an absolute must